1998
DOI: 10.1086/513951
|View full text |Cite
|
Sign up to set email alerts
|

Difficult‐to‐Treat Trichomoniasis: Results with Paromomycin Cream

Abstract: Vaginal trichomoniasis poses a difficult therapeutic challenge when metronidazole is ineffective or contraindicated. We conducted a retrospective study of 6.25% paromomycin cream in the treatment of nine women referred with cases of vaginal trichomoniasis where metronidazole resistance or allergy was present. Results obtained immediately and 1 month after treatment were reviewed. The median age of the patients was 46 years; four women were nulliparous. The median symptom duration was 1 year. Five women were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…Pulmonary infections caused by other trichomonads such as P. hominis, a parasite of the gastrointestinal tract, or T. vaginalis, a pathogen of the genitourinary system, are very unusual (4,6). However as clinical resistance and in vitro resistance to metronidazole have been regularly reported for T. vaginalis, species characterization by molecular methods is of clinical importance (1,5,8,12,14).…”
mentioning
confidence: 99%
“…Pulmonary infections caused by other trichomonads such as P. hominis, a parasite of the gastrointestinal tract, or T. vaginalis, a pathogen of the genitourinary system, are very unusual (4,6). However as clinical resistance and in vitro resistance to metronidazole have been regularly reported for T. vaginalis, species characterization by molecular methods is of clinical importance (1,5,8,12,14).…”
mentioning
confidence: 99%
“…Paromomycin* intravaginally 250 mg once or twice daily for 14 days -56-58% cure rate reported 78,80 Furazolidone* intravaginally 100 mg twice daily for 12-14 days -33% cure rate reported 72,81 Acetarsol* pessaries 500 mg nocte for 2 weeks 6% Nonoxynol-9* pessaries nightly for 2 weeks Availability *The medicines suggested for use in treatment failure are unlicensed products and may not be readily available for purchase in the UK. The pharmacy purchasing department may be able to source some of these products from specialist manufacturers.…”
Section: Other Treatments With Some Reported Success (Evidence Level mentioning
confidence: 99%
“…Nyirjesy et al [20] reported considerable success with topical paromomycin cream. Unfortunately, paromomycin is not widely available and its use has been associated with a high frequency of local vulvovaginal irritation and toxicity.…”
Section: Trichomoniasismentioning
confidence: 99%